Comment on “Nanoparticles impacts on natural convection nanofluid flow and heat transfer inside a square cavity with fixed a circular obstacle” [Case Studies in Thermal Engineering, 44 (2023) 102829] - Soumyanil Sadhu Deep; Sayma Sultana; Tahsin-Ul Haque; Md Tanvir Rahman; Sumon Saha (Case Studies in Thermal Engineering, 2025)
The following comments identify incorrect transport mechanisms, missing physical dimensions, missing physical parameters, undefined variables, incorrect governing equations and boundary conditions, incorrect/missing references, incorrect/missing thermo-physical properties, incorrect selection of controlling parameter's range, incorrect finite element formulations and missing information on all governing parameters in the qualitative and quantitative outcomes of the concerned paper. As a result, this inquiry examines and rectifies the above-mentioned publication.